Trusts without equity in the common law - Swadling, W (Deutscher Fachverlag GmbH, 2019)
It is a view prevalent amongst both English lawyers and comparative lawyers that the institution of the trust in the common law depends on there being a separate jurisdiction called Equity. The purpose of this article is to challenge that view. It describes both what it is that an English lawyer knows as Equity and the institution of the trust. It then outlines and refutes a number of possible objections to trusts existing in the common law without Equity.